Foundations of forensic vocational rehabilitation - Robinson, Rick H. (Springer Publishing Company, LLC, 2014)
This is the first fundamental text to focus specifically on forensic vocational rehabilitation, a field that is forecast to grow rapidly. Forensic vocational rehabilitation consultants evaluate the vocational and rehabilitation needs of individuals in an array of legal settings such as civil litigation, workers' compensation, Social Security disability, and others. The text is unique in its exploration of the vocational rehabilitation process from a biopsychosocial perspective that views disability as a complex and multidimensional construct. The book comprehensively describes the parameters a.